Behavioral traits of the arboreal marsupial Dromiciops gliroides during Tristerix corymbosus fruiting season - Di Virgilio, Agustina Soledad (2014)
The importance of a frugivore?s behavior and movement on seed dispersal patterns, although widely recognized, is sometimes difficult to obtain. This is particularly true for small and nocturnal animals that inhabit structurally complex environments, such as Dromiciops gliroides. We studied different behavioral traits of this species in its natural environment during the fruiting season of the mistletoe Tristerix corymbosus. Using videos recorded by camera traps, we obtained data regarding activity levels, time allocation, feeding patterns, and movement velocities of this frugivore. Our results showed that this small marsupial seemed to avoid moonlight, and to balance the costs generated by feeding during brightest nights (i.e., when more conspicuous to predators) feeds at higher rates than during less-illuminated nights. Feeding pattern analyses showed that D. gliroides can consume between 1 and 10 fruits per plant, but generally consumes 3 fruits. We also observed that the mean time needed for D. gliroides to extract and manipulate a fruit was 6 s. Time allocation analyses showed that, on average, individuals stayed on T. corymbosus and its hosts for 55 s, and allocate most of that time on feeding and moving within the mistletoe. Video analyses were demonstrated to be a useful sampling technique, which, in addition to allowing us to obtain information about activity patterns, also permitted us to assess fruit consumption patterns, visit lengths, and time allocation when visiting mistletoe. Moreover, video allowed us to understand the variability of movement velocities under different behavioral states. The information we provide here could be included into models to simulate seed dispersal in a more realistic and accurate way that incorporates not only spatial distribution of resources, but also detailed behavioral information of frugivores.